2007
DOI: 10.1038/nrc2196
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D signalling pathways in cancer: potential for anticancer therapeutics

Abstract: Epidemiological studies indicate that vitamin D insufficiency could have an aetiological role in various human cancers. Preclinical research indicates that the active metabolite of vitamin D, 1alpha,25(OH)2D3, also known as calcitriol, or vitamin D analogues might have potential as anticancer agents because their administration has antiproliferative effects, can activate apoptotic pathways and inhibit angiogenesis. In addition, 1alpha,25(OH)2D3 potentiates the anticancer effects of many cytotoxic and antiproli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
1,154
0
34

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,241 publications
(1,234 citation statements)
references
References 151 publications
20
1,154
0
34
Order By: Relevance
“…In the first step 7-dehydrocholesterol is converted into vitamin D 3 in the skin after exposures to UV radiation. Vitamin (Deeb et al, 2007). Degradation of unneeded 1α 25(OH) 2 D 3 is accomplished by the enzyme CYP24A1 (24 Hydroxylase) for regulation of 1α 25( OH) 2 D 3 synthesis.…”
Section: Mechanisms Of Action Of Vitamin Dmentioning
confidence: 99%
“…In the first step 7-dehydrocholesterol is converted into vitamin D 3 in the skin after exposures to UV radiation. Vitamin (Deeb et al, 2007). Degradation of unneeded 1α 25(OH) 2 D 3 is accomplished by the enzyme CYP24A1 (24 Hydroxylase) for regulation of 1α 25( OH) 2 D 3 synthesis.…”
Section: Mechanisms Of Action Of Vitamin Dmentioning
confidence: 99%
“…Many epidemiological and animal studies indicate that the active vitamin D metabolite 1a, 25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ) affords protection against colon cancer (Campbell and Adorini, 2006;Deeb et al, 2007;Eelen et al, 2007). A causal link between vitamin D deficiency and colon cancer has recently been considered probable by the International Agency for Research on Cancer (IARC, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1,25-Dihydroxyvitamin D 3 (calcitriol) has now received much interest for its anti-tumor activity (Deeb et al, 2007), although it is well known as a regulator of calcium and bone homeostasis. Most of the biological effects of calcitriol are elicited by the binding to VDR (Carlberg and Polly, 1998).…”
Section: Cyp24 and Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…Calcitriol is then inactivated by CYP24, a key metabolic enzyme, 9 the expression of which is regulated by VDR (Chen and DeLuca, 1995). It has been reported that CYP24 (Deeb et al, 2007) and VDR (Friedrich et al, 2002;Khadzkou et al, 2006) are overexpressed in various cancers. We found that both human CYP24 and VDR ) are post-transcriptionally regulated by miR-125b.…”
Section: Cyp24 and Vitamin D Receptor (Vdr)mentioning
confidence: 99%